Interação da proteina e2 do vírus da hepatite c com o receptor de ldl e cd81 presentes em células endoteliais e ativação da resposta inflamatória - Urbaczek, Ana Carolina [UNESP] (2012)
Approximately 170 million people worldwide are chronically infected with hepatitis C virus (HCV). In Brazil, the numbers have already reached 3 million. The persistence of HCV infection leads to chronic infection in liver disease, cirrhosis and hepatocellular carcinoma. The envelope protein 2 (E2) of HCV is responsible for its coupling to the host cell through interaction with cell surface receptors such as the R-LDL and CD81, among others. Because changes in micro and macrovasculature liver, have been identified as key elements in the histogenesis and prognosis of the disease, the aim of this study was to evaluate the interaction of the protein E2 recombinant with the R-LDL present on the surface of endothelial cells (HUVEC and ECV304) under the influence of LDL and protein glycosylation. And also evaluate the inflammatory response of endothelial cells to interact with these proteins. The E2 protein was expressed in two heterologous systems, E. coli and P. pastoris for evaluation of glycosylation and interaction with LDL binding to the R-LDL cells by flow cytometry. The proteins were also evaluated in biological tests for induction of cellular production of reactive oxygen species (EROs - QL and H2O2 - flow cytometry), NO (QL in doing gas and Griess Reagent), arginase (spectrophotometry), IL-8 (ELISA), VEGF (ELISA) and cell death (MTT – spectrophotometry and Annexin V and PI - flow cytometry). The results obtained showed that the recombinant E2 protein can interact with R-LDL endothelial cell after binding to LDL and that this binding can be enhanced by glycosylation (E2L) (p <0.01 in relation to E2B). The NO test indicated that glycosylated proteins exhibit greater potential for the stimulation of the HUVEC cells (p <0.01 compared with negative control). Protein concentrations tested were not sufficient to stimulate an increase or decrease in the activity of arginase remarkable compared to the negative control. The recombinant protein ...